Factors that influence the successful marketing of bioplastic products in Zimbabwe: Towards a circular economy by 2030 - Emmanuel, Mutambara; Joe, Muzurura (International Journal of Innovative Research and Scientific Studies, 2023)
Bioplastics are eco-friendly products that are not only highly bio-gradable and compositable, but also have robust rheological properties compared to fossil-based plastic products. Given the huge quantity of fossil-based plastics that are produced and consumed annually in Zimbabwe, consumers’ acceptance of these products may assist the country to smoothly transitioning from the current linear economic system (LES) towards a circular economic system (CES). The main purpose of the study was to explore factors that might influence the successful marketing of bioplastic products by Zimbabwe firms. With the aid of a structural regression equation, the study used a correlational design where quantitative data were collected from a random sample of 100 respondents. The findings show that self-identity, perceived value, cognitive biases and self-congruity were all positive and statistically significant at various levels of confidence. Zimbabwe plastic firms should consider these factors if they are to successfully implement strategies that increase the acceptance of bioplastic products. The adoption of discontinuous green technologies that reduce the cost of producing bioplastic products is recommended in order to increase the perceived value of bioplastics. Marketing efforts that help to increase consumers’ awareness and hence acceptance of bioplastic products must be adopted by firms.